Features of the approach the Great Prophet Muhammad in Education (Journal Of Educational and Psychological Researches, 2022)
God sent the Prophet Muhammad as a teacher and promising harbinger {that is sent to the illiterate messenger reciting to them His signs and purifies them and teaches them the Book and Wisdom} [Friday: 2]; the wisdom of Baos Prophet him peace be and am back to teach people, - Education and therefore his life was very rich educational tactics And has passed the Prophet in different circumstances and conditions that can be experienced by a teacher or educator in any time, anywhere; there is no case of going through the educator or teacher only finds the same or similar or likened to, or close to it in the life of the Prophet peace be upon him Prophet has lived God's peace be upon his strengths and weaknesses, victory and defeat, he lived orphanhood and paternity .. was deals with every stage and every case including matching. Prophet has treated with the community groups, and called on them, and taught them the best upbringing; with the rigors of their hearts and the roughness of morals, and staleness temperament and repulsion moods, Vaanml Prophet (peace be upon him) what are its staleness, and patience them harm, so they the best nation after it did not have the value and weight of {although they had been before in manifest error that the biography of the Prophet Mohammed and directed educational classes of society and is essential for the breeding source, which besides a great educational school came Avmaz men, and professors of generations, and the masters of thought, and the teachers of morality; one of them was an imam to pray, and a judge in the litigation, and preacher in the communities, and in mufti issues. The most important recommendations that came out of the search: ensuring young people and warn them of places sedition, or delve into the similarities and youth Welfare follow the safety of their faith and concern for the wisdom in the calendar Aauajjaj